Infarto agudo do miocárdio: um estudo retrospectivo em um hospital de referência da cidade de Belém - MACIEL, Rafael da Silva (2019)
The Acute Myocardial Infarction (AMI) is one of the more serious consequences for people with cardiovascular disease. This study is retrospective, descriptive with quantitative approach. Aimed to the following: a) identify the main risk factors presented by patients suffering from acute myocardial infarction admitted to a hospital of reference in Belém do Pará b) show the influence of risk factors and lifestyle factors as triggers for the episode of AMI, and c) identifying the epidemiological profile of infarcted patients. The sample comprised patients with diagnosis of AMI admitted to the Fundação Hospital de Clínicas Gaspar Viana in the years 2007 and 2008. Data were collected from 80 charts, with 40 of each year which equates to 24.1% and 31.7% respectively. Data collection occurred in the period from 20 to 30 May in the year 2009, could be identified where the major cardiovascular risk factors for AMI. Most of the sample, which was diagnosed infarction had between 51 to 90 years and the modifiable risk factors like hypertension, diabetes, sedentary lifestyle, smoking continue raising the mortality rates of AMI. The infarction is a preventable disease, where people practice and maintain healthy lifestyles. Want to contribute to the nursing professionals to acquire more knowledge about the subject and, increasingly, to humanize nursing care to patients and to stop more people becoming victims of AMI.